INDONESIA'S ECONOMIC DIPLOMACY STRATEGY TO TOYOTA MOTOR CORPORATION IN THE POLICY OF LOCAL CONTENT REQUIREMENTS IN THE NATIONAL CAR INDUSTRY POST-REFORMATION - Givari, Hilwan (Universitas Nasional, 2024)
The Indonesian government's policy of local content requirements (LCRs) in the national car industry represents a significant initiative aimed at increasing sustainable added value for the national economy. This study examines how Indonesia, through its Domestic Component Level (TKDN) program, has encouraged foreign car manufacturers, including Japan’s Toyota Motor Corporation (TMC), which holds over 36% of the market share, to support this initiative. The success of the program is closely linked to the government's use of economic diplomacy, which navigates domestic economic conditions as well as bilateral and multilateral relations. Using a qualitative approach through secondary data and a review of national and international regulations related to LCRs, this paper explores the Indonesian government’s economic diplomacy strategies towards TMC within the context of both domestic and bilateral frameworks. Furthermore, the analysis considers key factors, including the significance of the Indonesian automotive market and the challenges posed by the current trade regime of the World Trade Organization (WTO), while highlighting the strategic interests of Japanese multinational corporations in Indonesia’s automotive manufacturing industry